Estradiol Binds to Insulin and Insulin Receptor Decreasing Insulin Binding in vitro - Root-Bernstein, Robert; Podufaly, Abigail; Dillon, Patrick F. (Frontiers in Endocrinology, 2014)
Rationale: Insulin resistance associated with hyperestrogenemias occurs in gestational diabetes mellitus, polycystic ovary syndrome, ovarian hyperstimulation syndrome, estrogen therapies, metabolic syndrome and obesity. The mechanism by which insulin and estrogen interact is unknown. We hypothesize that estrogen binds directly to insulin and the insulin receptor producing insulin resistance. Objectives: To determine the binding constants of steroid hormones to insulin, the insulin receptor, and insulin-like peptides derived from the insulin receptor; and to investigate the effect of estrogens on the binding of insulin to its receptor. Methods: Ultraviolet spectroscopy, capillary electrophoresis and NMR demonstrated estrogen binding to insulin and its receptor. Horse-radish peroxidase-linked insulin was used in an ELISA-like procedure to measure the effect of estradiol on binding of insulin to its receptor. Measurements: Binding constants for estrogens to insulin and the insulin receptor were determined by concentration-dependent spectral shifts. The effect of estradiol on insulin-HRP binding to its receptor was determined by shifts in the insulin binding curve. Main Results: Estradiol bound to insulin with a Kd of 12 x 10-9 M and to the insulin receptor with a Kd of 24 x 10-9 M, while other hormones had significantly less affinity. 200 nM estradiol shifted the binding curve of insulin to its receptor 0.8 log units to the right. Conclusions: Estradiol concentrations in many hyperestrogenemic syndromes are sufficient to interfere with insulin binding to its receptor producing significant insulin resistance.